Association between serum osmolality and risk of in-hospital mortality in patients with intracerebral hemorrhage - Hu, Zhaosuo; Sha, Quan (Frontiers in Neurology, 2024)
Aim: This study aimed to analyze the association between serum osmolality and the risk of in-hospital mortality in intracerebral hemorrhage (ICH) patients. Methods: In this cohort study, a total of 1837 ICH patients aged ≥18 years from the Medical Information Mart for Intensive Care-IV (MIMIC-IV) were identified. Serum osmolality and blood urea nitrogen (BUN) to creatinine (Cr) ratio (BCR) were used as the main variables to analyze their association with the risk of in-hospital mortality in ICH patients after first intensive care unit (ICU) admission, and univariate Cox model was established. Univariable and multivariable Cox regression analysis were applied to explore the associations among serum osmolality and BCR with the in-hospital mortality of ICH patients. Hazard ratio (HR), and 95% confidence interval (CI) were calculated. Results: The median survival time of all participants was 8.29 (4.61-15.24) days. Serum osmolality ≥295 mmol/L was correlated with increased risk of in-hospital mortality in patients with ICH (HR=1.43, 95%CI: 1.14-1.78). BCR >20 was not significantly associated with the risk of in-hospital mortality in patients with ICH. Subgroup analysis indicated that increased risk of in-hospital mortality was found in ICH patients who were females, White, Black, or complicated with acute kidney injury (AKI). Conclusion: High serum osmolality was related to increased risk of in-hospital mortality in patients with ICH.